Leukoencephalopathy with ataxia, hypodontia, and hypomyelination - Wolf, Nicole; Harting, Inga; Boltshauser, E.; Wiegand, G.; Koch, Martin Jean; Schmitt-Mechelke, T.; Martin, E.; Zschocke, Johannes; Uhlenberg, B.; Hoffmann, Georg F.; Weber, L.; Ebinger, Friedrich; et al. (Neurology, 2005)
The authors describe four unrelated girls with a distinctive neurologic disorder with early-onset progressive ataxia and hypodontia with a characteristic pattern of delayed dentition. Cerebral MRI shows hypomyelinated white matter and cerebellar atrophy; 1H-MRS of white matter reveals a marked elevation of myo-inositol.
Gesehen am 17.03.2021